Post grafted gallic acid to chitosan-Ag hybrid nanoparticles via free radical-induced grafting reactions - GÜNDÜZ, OĞUZHAN (My University, 2023)
© 2023The present study proposes two unique systems using free radical-induced grafting reactions to combine Ag, chitosan (CS) and gallic acid (GA) into a single particulate nanostructure. GA-grafted-CS (GA-g-CS) was used to reduce Ag+ to Ag0, and producing Ag-GA-g-CSNPs (hybrid NPs I). Also, GA was grafted into CS–AgNPs, to form GA-g-CS AgNPs (hybrid NPs II). Although there were previous attempts to graft GA into CS, this is first time to graft GA into CS–AgNPs. The study aimed to enhance biocompatibility, antibacterial and antioxidant properties of CS–AgNPs via grafted GA. Grafting GA into CS–AgNPs was confirmed by UV–Vis, DLS, DSC/TGA, XRD, EDX and FTIR. The morphology and size of NPs were studied by TEM and SEM. The decrease of ζ-potential from +50 mV in CS-Ag NPs to +33 and + 29 mV, in the presented 2 nanoforms hybrid NPs I and II, respectively, is an indication for the successful GA graft. Among all samples, hybrid NPs II showed lower toxicity, higher antioxidant and antibacterial activity. The obtained results revealed that grafting GA to CS–AgNPs, as a new method to combine Ag, CS and GA in a uniparticulate structure, is a unique process which may deserve a more future consideration.
Keywords: Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sitogenetik; Temel Bilimler; Life Sciences; Molecular Biology and Genetics; Cytogenetic; Natural Sciences; Yaşam Bilimleri (LIFE); BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; Life Sciences (LIFE); MOLECULAR BIOLOGY & GENETICS; BIOCHEMISTRY & MOLECULAR BIOLOGY; Yapısal Biyoloji; Biyokimya; Moleküler Biyoloji; Structural Biology; Biochemistry; Molecular Biology; Antibacterial and antioxidant activity; Chitosan–Ag nanoparticles; Gallic acid